WEB GIS for Mapping the Locations of Licensed Midwifery Practices in the Asahan Region - Kalsum, Ummi; Sembiring, Muhammad Ardiansyah; Rohminatin, Rohminatin (Electronic Journal of Education, Social Economics and Technology, 2025)
The advancement of digital technology has significantly impacted the healthcare sector, offering innovative ways to improve service accessibility and quality. One such advancement is the use of Geographic Information Systems (GIS), which enables the integration and visualization of spatial and non-spatial data. This research focuses on the development of a Web GIS platform designed to map the locations of licensed midwifery practices in Asahan Regency. The primary goal is to provide the public with easier access to valid health service information and to assist local authorities in monitoring and managing these services more efficiently. The system was developed using PHP (CodeIgniter framework), MySQL for data storage, and Leaflet for interactive mapping functionalities. Using a qualitative research methodology, data were collected through observation, interviews with relevant stakeholders, and literature review. The system displays midwife practice locations along with critical attributes such as licensing information, service types, and operational hours. It also features user interaction capabilities through a review and feedback mechanism. The innovation presented in this study lies in the integration of legality data into a public-facing, interactive spatial information platform—an aspect rarely addressed in existing health GIS applications in Indonesia. Testing demonstrated that the system meets functional requirements, ensures ease of use, and delivers accurate, real-time information. The developed system offers a replicable model that can be applied in other regions to support transparent and informed decision-making in maternal healthcare services.